Natalia Obrenovich (Keshko) – the queen, the mother and the wife. The story of her of rise and fall - Zabolotnaia, Lilia (Balcanica Posnaniensia. Acta et studia, 2020)
Natalia Obrenovich (Keshko) – the queen, the mother and the wife. The story of her of rise and fall In the article, an attempt was made to reconstruct some fragments from the life of Natalia Obrenović, nee Keshko, through the prism of her personal, emotional perception of the events: marriage, family life, divorce and separation from her son.The main sources of research are documents from the Russian archives (letters, newspaper articles, memoirs). The author suggests that the marriage had far-reaching, visionary plans for dynastic merging and strengthening the position of the Moldavian-Serbian aristocracy in the Balkans. However, the marriage did not work out due to a number of circumstances: because of family strife, incompatibility of characters, but especially because of the difference in political views. In the history of the tragic disintegration of the family, Natalya’s imperious disposition and her desire to rule the country played an important role. The microhistorical approach and the interdisciplinary principle of research make it possible to study in detail the particular phenomena (divorce, separation from the son) that took place in the life of our heroine in the context of prevailing ideas and trends in society.